Comparison of in vivo and in vitro models to evaluate pulp temperature rise during exposure to a Polywave® LED light curing unit - Patricio Runnacles; Cesar Augusto Galvão Arrais; Cristiane Maucoski; Ulisses Coelho; Mario Fernando De Goes; Frederick Allen Rueggeberg (University of São Paulo, 2019)
Abstract Objectives: To measure and compare in vivo and in vitro pulp temperature (PT) increase (ΔTEMP) over baseline, physiologic temperature using the same intact upper premolars exposed to the same Polywave® LED curing light. Methodology: After local Ethics Committee approval (#255,945), local anesthesia, rubber dam isolation, small occlusal preparations/minute pulp exposure (n=15) were performed in teeth requiring extraction for orthodontic reasons. A sterile probe of a temperature measurement system (Temperature Data Acquisition, Physitemp) was placed within the pulp chamber and the buccal surface was sequentially exposed to a LED LCU (Bluephase 20i, Ivoclar Vivadent) using the following exposure modes: 10-s low or high, 5-s Turbo, and 60-s high. Afterwards, the teeth were extracted and K-type thermocouples were placed within the pulp chamber through the original access. The teeth were attached to an assembly simulating the in vivo environment, being similarly exposed while real-time temperature (°C) was recorded. ΔTEMP values and time for temperature to reach maximum (ΔTIME) were subjected to two-way ANOVA and Bonferroni's post-hoc tests (pre-set alpha 0.05). Results: Higher ΔTEMP was observed in vitro than in vivo. No significant difference in ΔTIME was observed between test conditions. A significant, positive relationship was observed between radiant exposure and ΔTEMP for both conditions (in vivo: r2=0.917; p<0.001; in vitro: r2=0.919; p<0.001). Conclusion: Although the in vitro model overestimated in vivo PT increase, in vitro PT rise was close to in vivo values for clinically relevant exposure modes.